ASSESSMENT OF LEVEL OF ANXIETY AND DEPRESSION AMONG PEOPLE LIVING WITH CANCER IN SELECTED CANCER HOSPITAL KOLKATA, WEST BENGAL - Mondal, Mithu; Chudhuri, Moitreyee; Maity, Chandrima (International Journal of Research -GRANTHAALAYAH, 2023)
Introduction: A cancer diagnosis can have a wide-ranging impact on mental health. The prevalence of anxiety and depression among people with cancer is high among those with no previous psychiatric history. Aim: This study aims to find out anxiety and depression among people living with cancer and association between anxiety, depression and selected demographic variables. Methods: A descriptive study was conducted to detect the level of anxiety and depression and association them with demographic variables. Total 200 participants were selected through non- robability purposive sampling technique. In this study the conceptual framework was based on Rosenstock, Strecher, and Becker Health Belief Model. Data were collected through semi structured questionnaire, GAD-7 Questionnaire and PHQ-9 Questionnaire to assess socio-demographic information, level of anxiety and depression respectively. Result: Results revealed that 51% people living with cancer had mild anxiety and 10% participants had severe level of anxiety; 31% participants had major depression mild and only 5% had severe level of depression. Chi-square test revealed that there was a significant relationship between anxiety with religion, monthly income and social support and level of depression of people living with cancer were significantly associated with age and social support at the (P<0.05) and (P<0.001) level of significant. Conclusion: The people living with cancer had different level of anxiety and depression. Moreover, anxiety of people living with cancer is associated with religion, monthly income and social support and depression is associated with age and social support.